Wound healing and Cadmium detoxification in the earthworm Lumbricus terrestris – a potential case for coelomocytes? - Aigner, Gerhard P.; Peer, Veronika; Fiechtner, Birgit; Piechnik, Cláudio Adriano; Höckner, Martina (Frontiers in Immunology, 2023)
Earthworms are affected by physical stress, like injury, and by exposure to xenobiotics, such as the toxic metal cadmium (Cd), which enters the environment mainly through industry and agriculture. The stress response to the single and the combination of both stressors was examined in regenerative and unharmed tissue of Lumbricus terrestris to reveal if the stress response to a natural insult like injury (amputation) interferes with Cd detoxification mechanisms. We characterized the roles of MT1 and MT2 isoforms, HSP70 as well as immune biomarkers such as the toll-like receptors sccTLR and mccTLR. The role of the transcription factors ATF2, ATF7, and CREB as putative regulatory intersection as well as a stress-dependent change of the essential trace elements zinc and calcium was analyzed. P-AMPK, the cellular energy sensor, was measured to explore the energy demand, while the energy status was determined by detecting carbohydrate and protein levels. Taken together, we were able to show that injury rather than Cd is the driving force that separates the four treatment groups -Control, Cd exposure, Injury, Cd exposure and injury. Interestingly, we found that gene expression differed regarding the tissue section that was analyzed and we hypothesize that this is due to the migration of coelomocytes, earthworm immune cells, that take over a key role in protecting the organism from a variety of environmental challenges. Surprisingly, we discovered a role for MT1 in the response to multiple stressors and an isoform-specific function for the two newly characterized TLRs. In conclusion, we gathered novel information on the relation of innate immunity, wound healing, and Cd detoxification mechanisms in earthworms.